2017
DOI: 10.1056/nejmoa1613849
|View full text |Cite
|
Sign up to set email alerts
|

Trial of Tocilizumab in Giant-Cell Arteritis

Abstract: Tocilizumab, received weekly or every other week, combined with a 26-week prednisone taper was superior to either 26-week or 52-week prednisone tapering plus placebo with regard to sustained glucocorticoid-free remission in patients with giant-cell arteritis. Longer follow-up is necessary to determine the durability of remission and safety of tocilizumab. (Funded by F. Hoffmann-La Roche; ClinicalTrials.gov number, NCT01791153 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
896
3
49

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,085 publications
(976 citation statements)
references
References 26 publications
28
896
3
49
Order By: Relevance
“…A recent report that treatment of PMR with modest doses of CSs is devoid of devastating long-term side effects [7] is not universally accepted [8], and does little to clarify the confusion. There exists a long list of DMARD's that can be tested, including il-6 inhibitors [9], but since this latter medication is now utilized for its CSs sparing effect in biopsy proven GCA [10], such studies need to be properly designed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report that treatment of PMR with modest doses of CSs is devoid of devastating long-term side effects [7] is not universally accepted [8], and does little to clarify the confusion. There exists a long list of DMARD's that can be tested, including il-6 inhibitors [9], but since this latter medication is now utilized for its CSs sparing effect in biopsy proven GCA [10], such studies need to be properly designed.…”
Section: Discussionmentioning
confidence: 99%
“…Several case series and retrospective studies have highlighted the potential efficacy of the anti-interleukin 6 receptor tocilizumab (TCZ) in PMR and GCA (37)(38)(39). The Gi-ACTA trial (40), which tested the effect of TCZ in patients with GCA, showed impressive results regarding both remission rate and cumulative steroid dose, leading to the approval of TCZ by FDA as a breakthrough therapy for GCA. In contrast to GCA, the potential benefit of TCZ for treatment of PMR is less clear.…”
Section: Biologic Dmardsmentioning
confidence: 99%
“…There are currently no published guidelines for using steroid-sparing immunomodulatory agents; however, there is growing evidence for use of anti-interleukin-6 (tocilizumab) as well as T cell costimulation inhibition (abatacept) along with corticosteroids to decrease GCA relapse rate and improve outcomes. 7,8 Management of GCA-related stroke requires potent immunosuppression with high-dose systemic corticosteroids. Pulse dosing or 1-2 mg/kg/d of methylprednisolone have been used but neither dosing regimen has been found superior.…”
Section: Sectionmentioning
confidence: 99%